Comparative Genome Analysis Across 128 Phytophthora Isolates Reveal Species-Specific Microsatellite Distribution and Localized Evolution of Compartmentalized Genomes - Mandal, Kajal; Dutta, Subhajeet; Upadhyay, Aditya; Panda, Arijit; Tripathy, Sucheta (Frontiers in Microbiology, 2022)
Phytophthora species are invasive groups of pathogens belonging to class Oomycetes. In order to contain and control them, deep knowledge of their biology and infection strategy is imperative. With the availability of large-scale sequencing data, it has been possible to look directly into their genetic material and understand the strategies adopted by them for becoming successful pathogens. Here we have studied the genomes of 128 Phytophthora species available publicly with reasonable quality. Our analysis reveals that the Simple Sequence Repeats (SSRs) of all Phytophthora sp. follow distinct isolate specific patterns. We further show that TG/CA dinucleotide repeats are far more abundant in Phytophthora sp. than other classes of repeats. In the case of tri and tetranucleotide SSRs also TG/CA containing motifs always dominate over others. GC content of the SSRs is stable without much variation across the isolates of Phytophthora. Telomeric repeats of Phytophthora follow a pattern of (TTTAGGG)n or (TTAGGGT)n rather than the canonical (TTAGGG)n. RxLR motifs containing effectors diverge rapidly in Phytophthora and do not show any core common group. RxLR effectors of some Phytophthora isolates have a tendency to form clusters with RxLRs from other species than within the same species. Analysis of the Flanking Intergenic Distance clearly indicates a two speed genome organization for all the Phytophthora isolates. Apart from effectors and the transposons, a large number of other virulence genes such as Cazymes, transcriptional regulators, signal transduction genes, ABC transporters, ubiquitins are also present in the repeat-rich compartments. This indicates a rapid co-evolution of this powerful arsenal for successful pathogenicity. Whole genome duplication studies indicate the pattern followed is more specific to a geographic location. To conclude, large-scale genomic studies of Phytophthora have thrown light on their adaptive evolution, which is largely guided by the localized host-mediated selection pressure.